Ethical and Regulatory Issues for Embedded Pragmatic Trials Involving People Living with Dementia. (26th June 2020) - Largent, Emily A.; Hey, Spencer Phillips; Harkins, Kristin; Hoffman, Allison K.; Joffe, Steven; Lima, Julie C.; London, Alex John; Karlawish, Jason
Abstract : Embedded pragmatic clinical trials (ePCTs) present an opportunity to improve care for people living with dementia (PLWD) and their care partners, but they also generate a complex constellation of ethical and regulatory challenges. These challenges begin with participant identification. Interventions may be delivered in ways that make it difficult to identify who is a human subject and therefore who needs ethical and regulatory protections. The need for informed consent, a core human subjects protection, must be considered but can be in tension with the goals of pragmatic research design. Thus it is essential to consider whether a waiver or alteration of informed consent is justifiable. If informed consent is needed, the question arises of how it should be obtained because researchers must acknowledge the vulnerability of PLWD due in part to diminished capacity and also to increased dependence on others. Further, researchers should recognize that many sites where ePCTs are conducted will be unfamiliar with human subjects research regulations and ethics. In this report, the Regulation and Ethics Core of the National Institute on Aging Imbedded Pragmatic Alzheimer's disease (AD) and AD‐related dementias (AD/ADRD) Clinical Trials (IMPACT) Collaboratory discusses key ethical and regulatory challenges for ePCTs in PLWD. A central thesis is that researchers should strive to anticipate and address these challenges early in the design of their ePCTs as a means of both ensuring compliance and advancing science. J Am Geriatr Soc 68:S37–S42, 2020 .